Intestinal ischemia in abdominal aortic reconstructive surgery - Goller, Wolfgang G.; Mazza, Milton; Fernández Perdomo, Gonzalo; Torterolo, Edgardo; Burstin, Jacobo; Nozar, José V.; Rinaldi, Bruno (Cirugía del Uruguay, 1982)
Intestinal ischemia is a serious complication of the repairing surgery of the abdominal aorta; generally involving the Jeft colon and more rarely the small intestine or both simultaneously. It is more frequent as a complication of an aneurysmectomy. The incidence of this complication is 0.2 to 10% of the cases. The authors have observed this complication seven times in 216 cases of repairing surgery of the abdominal aorta (3.24%). The global mortality of ischemic colitis is 40%, when the whole intestinal wall is ischemic mortality rises to 90%. 5 of the seven cases observed by the authors died (71.42%) The authors discuss the different factors that might cause the development of an intestinal ischemia. The prevention of this complication by means of pre and postoperative care is also discussed. Emphasis is made upon the c!inical features that lead to the correct diagnosis of the established ischemia, and the additional testing methods to certify it.